Pengaruh Media Iklan dan Citra Merek Terhadap Loyalitas Konsumen Pada Produk Teh Botol Sosro (Studi Kasus: Konsumen Kota Bima) - Nur Magfira; Ismunandar Ismunandar (Journal of Business and Economics Research (JBE), 2020)
This study aims to determine the effect of advertising media on the purchase decision of sosro bottled tea products in Bima city consumers, determine the effect of brand image on sosro bottled tea purchasing decisions on Bima city consumers, find out the influence of advertising media and brand image on the sosro bottled tea product purchasing decisions in the consumers of the city of bima, the type of research used was associative research, the population in this study was sosro bottled tea consumers in the city of bma with a sample of 96 respondents who consumed livestock sosoro bottled tea using a purposive sampling technique. Data collection techniques in this study are observation, questionnaire form in the form of questionnaires and literature study to find the latest and related references related to the title of this article, data analysis used is validity, reliability, classic assumptions, multiple linear regression, correlation coefficient test and determination, partial test and simultaneous test, the results in this study are the results of the influence of advertising media variables on product purchasing decisions on sosro bottled tea by consumers in the city of bima, brand image influences the decision to purchase sosro bottled tea products by bima city consumers, there is influence advertising media and brand image of product purchasing decisions by consumers of the city of Bima